Low-alloying Mg-Zn-Ca magnesium alloy and preparation method and application thereof
By adding Zn and Ca elements to magnesium alloys, controlling their atomic ratio, and using low alloying and solid solution treatment processes, the challenges of magnesium alloys in high elongation and corrosion resistance are solved, and the high elongation of magnesium alloys are achieved and corrosion resistance reduces material costs.
Patent Information
- Application Number
- CN202411250250.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-20
AI Technical Summary
Magnesium alloys have challenges in preparing high elongation and corrosion resistance, especially in the field of implanted medical devices and batteries, and the costly rare earth alloyed materials are not economical.
By adding a small amount of Zn and Ca elements to the magnesium alloy, the atomic ratio is controlled, and the low corrosion potential of Ca and the high corrosion resistance of Zn are used to inhibit the second phase of the magnesium alloy, and the low alloying and solid solution treatment are used, and the slow The fast extrusion process forms uniform and fine recrystallization structure to improve the strength and plasticity of the material.
Achieve high elongation (≥36%) and good corrosion resistance (corrosion rate is less than 0.25mm·y-1 in 3.5% aqueous NaCl solution), reducing the cost of the material and avoiding galvanic corrosion Phenomenon.
Smart Images

Figure CN119162496A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal materials and processing thereof, and in particular relates to a low-alloyed Mg-Zn-Ca magnesium alloy and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Magnesium alloys have good application prospects in the fields of implantable medical devices and metal-air batteries due to their good biocompatibility and high specific energy density. Magnesium alloys have only three slip systems at room temperature and cannot obtain high elongation and good plastic formability through coordinated deformation, which restricts the preparation of high-plasticity plates and bars in related fields. Currently, there are two main ways to improve the plasticity of magnesium alloys: rare earth alloying and low alloying. The former has a higher material cost, so low alloying has become a hot topic of research.
[0004] In addition, magnesium alloys are prone to self-corrosion in aqueous solutions containing chloride ions, while releasing a large amount of hydrogen. This has slowed down the application of magnesium alloys in implantable medical devices and batteries. How to prepare high-elongation and corrosion-resistant magnesium alloy materials is an urgent problem to be solved. Summary of the invention
[0005] In view of the above problems, the purpose of the present invention is to provide a low-alloyed Mg-Zn-Ca magnesium alloy and its preparation method and application. The present invention adds a small amount of Zn and Ca elements to the magnesium alloy, utilizes the lower corrosion potential of the Ca element and the high corrosion resistance of the Zn element, inhibits the formation of the second phase of the magnesium alloy material through low alloying, avoids galvanic corrosion between the magnesium alloy matrix and the second phase, and thus obtains a low-alloyed magnesium alloy with good corrosion resistance.
[0006] Specifically, the present invention provides the following technical solutions:
[0007] According to a first aspect of the present invention, a low-alloyed Mg-Zn-Ca magnesium alloy is provided, wherein the magnesium alloy is composed of the following elements in mass percentage: Zn 0.2% to 0.5%, Ca 0.2% to 0.4%, inevitable impurity elements, and the balance is Mg; the atomic ratio of Ca to Zn is higher than 2:3; the total mass percentage of the inevitable impurity elements is not higher than 0.03%, wherein: Fe<0.02%, Cu<0.002%, Ni<0.002%, Si<0.005%.
[0008] Preferably, the magnesium alloy is composed of the following elements in mass percentage: Zn 0.24-0.40%, Ca 0.22-0.28%, Fe<0.002%, Cu<0.0005%, Ni<0.0005%, Si<0.002%, and the balance is Mg.
[0009] Preferably, the magnesium alloy is composed of the following elements in mass percentage: Zn 0.32%, Ca 0.25%, Fe<0.002%, Cu<0.0005%, Ni<0.0005%, Si<0.002%, and the balance is Mg.
[0010] A second aspect of the present invention provides a method for preparing a low alloyed Mg-Zn-Ca magnesium alloy, comprising the following steps:
[0011] S1. Mix various raw materials, and then melt and refine them in sequence under protective gas to obtain a melt;
[0012] S2, casting the melt to obtain an ingot, and then performing heat treatment to obtain a billet;
[0013] S3. The billet is extruded to obtain a formed part, and after cooling, a magnesium alloy is obtained.
[0014] Preferably, in step S1, the raw materials are high-purity Mg, high-purity Ca and high-purity Zn; wherein the purity of metal Mg and Zn is greater than 99.98%, and the purity of metal Ca is greater than 99.9%.
[0015] Preferably, in step S1, the shielding gas is a mixture of CO2 and SF6, and the mixing ratio of CO2 and SF6 is 100-200:1; further preferably, the mixing ratio of CO2 and SF6 in the shielding gas is 100:1.
[0016] Preferably, in step S1, the smelting temperature is 720-760° C., and the smelting time is 40-60 min.
[0017] Preferably, in step S1, the refining time is 5 to 20 minutes.
[0018] Preferably, in step S1, the refining is followed by heat preservation and standing; further preferably, the standing time is 20 to 40 minutes.
[0019] Preferably, in step S1, during the refining process, the melt is stirred for 5 to 20 minutes.
[0020] Preferably, in step S2, the casting temperature is 680-700°C.
[0021] Preferably, in step S2, the heat treatment temperature is 350-440° C., and the heat treatment time is 1-64 hours.
[0022] Preferably, in step S3, the process of extruding the billet to obtain a formed part is specifically: using a horizontal extruder, extrusion molding at a speed of 0.05-0.5 mm / s; further preferably, the extrusion temperature is 250-350°C; and the extrusion ratio is 10-80.
[0023] The third aspect of the present invention provides the application of the low-alloyed Mg-Zn-Ca magnesium alloy described in the first aspect in the fields of implantable medical devices, metal-air batteries, etc.
[0024] One or more embodiments of the present invention have at least the following beneficial effects:
[0025] (1) The present invention adds a small amount of Zn and Ca elements to the magnesium alloy to prepare a low-alloyed magnesium alloy. Since the amount of Zn and Ca added is lower than their solid solubility in the magnesium alloy, a single-phase magnesium alloy structure can be obtained. A uniform and fine recrystallized structure is obtained by using solid solution treatment, slow extrusion, etc.; the lower extrusion temperature causes more defects such as vacancies, dislocations and stacking faults to form inside the grains, thereby promoting the segregation of Ca and Zn elements at the grain boundaries; grain refinement and segregation improve the strength of the material - tensile yield strength ≥170MPa, tensile strength ≥230MPa.
[0026] (2) The Ca element added to the magnesium alloy prepared by the present invention can weaken the basal texture of the deformed magnesium alloy and improve the plasticity of the material; the added Zn element can reduce the anisotropy of the critical shear stress (CRSS) of the basal, cylindrical and conical slip systems to a certain extent. Therefore, the magnesium alloy prepared by the present invention coordinates plastic deformation, grain boundary sliding of fine grains and very little second phase in the structure, so that the plasticity of the material is greatly improved - elongation ≥ 36%.
[0027] (3) The Ca added to the magnesium alloy prepared by the present invention has a slightly lower electrode potential than Mg, which will not cause anodic corrosion of the magnesium alloy, and the Pilling-Bedworth ratio of CaO to Mg is 1.17, that is, the corrosion product formed by Ca can inhibit the oxidation of the matrix; Zn first forms Zn(OH)2 in water, and then gradually transforms into Zn5Cl2(OH)8, which leads to the passivation state near the grain boundary of Zn segregation in a weak alkaline environment (the corrosion product initially formed by the Mg alloy in the NaCl solution is micro Mg(OH)2, which is slightly soluble in water to form a weak alkaline environment), thereby inhibiting the common intergranular corrosion phenomenon of magnesium alloys. Therefore, the corrosion resistance of the material of the present invention is greatly improved - the corrosion rate in a 3.5% NaCl aqueous solution is less than 0.25mm·y -1 , better than 0.3mm·y of high purity magnesium -1 ).
[0028] (4) The present invention forms a small amount of Ca2Mg6Zn3 (melting point over 410°C) and Mg2Ca (melting point 711°C) phases with low electrode potential and high melting point by regulating the content and ratio of Zn and Ca elements in the alloy, thereby avoiding the significant galvanic corrosion between the MgZn phase (melting point 341°C) with low melting point and high electrode potential and the magnesium matrix, and obtaining a low-alloyed magnesium alloy with good corrosion resistance. Studies have shown that when the addition amount of Ca exceeds 0.4wt%, a continuous network phase may be formed; if the atomic ratio of Ca to Zn is lower than 2:3, a MgZn phase may be formed inside the material, both of which will deteriorate the hot formability, mechanical properties and corrosion resistance of the material (the standard hydrogen electrode potentials of Ca, Mg and Zn are:
[0029] -2.87V, -2.34V and -0.762V).
[0030] (5) The magnesium alloy prepared by the present invention can be prepared by conventional equipment and conventional processes (no need to be processed by plastic forming process below 250°C), and the cost is relatively low. It is well known that as the forming temperature decreases, the grains can be significantly refined, and even nanocrystals can be obtained, thereby greatly improving the relevant properties. However, the magnesium alloy has a large deformation resistance during plastic processing below 250°C, which causes high loss to equipment and molds and high cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0032] Figure 1 The microstructure of the Mg-0.32wt%Zn-0.25wt%Ca magnesium alloy extruded rod prepared in Example 1 of the present invention;
[0033] Figure 2 This is the microstructure of the Mg-0.57wt%Zn-0.50wt%Ca magnesium alloy extruded rod prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0034] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0035] As mentioned above, there are currently two main ways to improve the plasticity of magnesium alloys: rare earth alloying and low alloying. The former has a higher material cost, so low alloying has become a hot topic of research. At present, magnesium alloys are prone to self-corrosion in aqueous solutions containing chloride ions, and a large amount of hydrogen is precipitated, which slows down the application of magnesium alloys in the fields of implantable medical devices and batteries. Therefore, the preparation of magnesium alloy materials with high elongation and corrosion resistance is an urgent problem to be solved.
[0036] A first typical embodiment of the present invention provides a low-alloyed Mg-Zn-Ca magnesium alloy, which is composed of the following elements in mass percentage: Zn 0.2% to 0.5%, Ca 0.2% to 0.4%, inevitable impurity elements, and the balance is Mg; the atomic ratio of Ca to Zn is higher than 2:3; the total mass percentage of the inevitable impurity elements is not higher than 0.03%, among which: Fe<0.02%, Cu<0.002%, Ni<0.002%, Si<0.005%.
[0037] In one or more examples of this implementation, the magnesium alloy is composed of the following elements in mass percentage: Zn 0.24-0.40%, Ca 0.22-0.28%, Fe<0.002%, Cu<0.0005%, Ni<0.0005%, Si<0.002%, and the balance is Mg.
[0038] In one or more examples of this implementation, the magnesium alloy is composed of the following elements in mass percentage: Zn 0.32%, Ca 0.25%, Fe<0.002%, Cu<0.0005%, Ni<0.0005%, Si<0.002%, and the balance is Mg.
[0039] A second typical embodiment of the present invention provides a method for preparing a low-alloyed Mg-Zn-Ca magnesium alloy, comprising the following steps:
[0040] S1. Mix various raw materials, and then melt and refine them in sequence under protective gas to obtain a melt;
[0041] S2, casting the melt to obtain an ingot, and then performing heat treatment to obtain a billet;
[0042] S3. The billet is extruded to obtain a formed part, and after cooling, a magnesium alloy is obtained.
[0043] In one or more examples of this implementation mode, in step S1, the raw materials are high-purity Mg, high-purity Ca and high-purity Zn; wherein the purity of metal Mg and Zn is greater than 99.98%, and the purity of metal Ca is greater than 99.9%.
[0044] In one or more embodiments of this implementation mode, in step S1, the protective gas is a mixture of CO2 and SF6, and the mixing ratio of CO2 and SF6 is 100-200:1; further preferably, the mixing ratio of CO2 and SF6 in the protective gas is 100:1.
[0045] In one or more examples of this embodiment, in step S1, the smelting temperature is 720-760° C., and the smelting time is 40-60 min.
[0046] In one or more examples of this implementation mode, in step S1, the refining time is 5 to 20 minutes.
[0047] In one or more examples of this implementation mode, in step S1, the refining is followed by heat preservation and standing; further preferably, the standing time is 20 to 40 minutes.
[0048] In one or more examples of this implementation mode, in step S1, during the refining process, the melt is stirred for 5 to 20 minutes.
[0049] In one or more examples of this embodiment, in step S2, the casting temperature is 680-700°C.
[0050] In one or more examples of this embodiment, in step S2, the heat treatment temperature is 350-440° C. and the temperature is kept for 1-64 hours.
[0051] In one or more examples of this embodiment, in step S3, the process of obtaining a formed part by extruding the billet is specifically as follows: a horizontal extruder is used to extrude the billet at a speed of 0.05 to 0.5 mm / s; further preferably, the extrusion temperature is 250 to 350°C; and the extrusion ratio is 10 to 80.
[0052] A third typical embodiment of the present invention provides application of the low-alloyed Mg-Zn-Ca magnesium alloy described in the first aspect in applications in the fields of implantable medical devices, metal-air batteries, etc.
[0053] The present invention homogenizes the Mg-Zn-Ca alloy at an appropriate temperature (solid solution treatment) to obtain a single magnesium alloy matrix phase and eliminate the uneven distribution of elements that may be caused by the casting process; then, a fine dynamic recrystallization grain structure is obtained by slow plastic deformation within a relatively low extrusion temperature range of 250 to 350°C. On the one hand, the slow deformation process facilitates the control of the temperature of the plastic deformation area; on the other hand, the defects such as vacancies, dislocations, and stacking faults formed during the low plastic deformation process promote the segregation of Ca and Zn at the grain boundaries.
[0054] The fine grains and the segregation of Ca and Zn at the grain boundaries synergistically reduce the common grain boundary corrosion phenomenon of magnesium alloys in salt water. Among them, the uniform fine grains promote grain boundary sliding; Ca weakens the texture of magnesium alloys and promotes the deformation coordination of the alloy; the segregation of Zn and Ca increases the strength at the grain boundaries and also avoids the common stress concentration around the second phase of magnesium alloys in the subsequent deformation process, forming crack sources, resulting in reduced plasticity. The coordination of the three improves the plasticity of magnesium alloys.
[0055] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0056] Example 1 : This embodiment provides a low-alloyed Mg-Zn-Ca magnesium alloy and a preparation method thereof.
[0057] A low-alloyed Mg-Zn-Ca magnesium alloy comprises the following element components in mass percentage: Zn 0.32%, Ca 0.25%, Fe<0.002%, Cu<0.0005%, Ni<0.0005%, Si<0.002%, and the balance is Mg.
[0058] The preparation method comprises the following steps:
[0059] S1. Ingredients: according to the proportion of magnesium alloy components, weigh high-purity Mg, high-purity Ca and high-purity Zn; the purity of metal Mg and Zn is greater than 99.98%, and the purity of metal Ca is greater than 99.9%.
[0060] S2. Melting and casting: melt the prepared magnesium alloy raw materials in sequence at 740°C under the protection of CO2+SF6 mixed gas (ratio 100:1) pure Mg, pure Ca and pure Zn, and keep warm for 40 minutes; refine and stir for 5 minutes, and keep warm and stand for 30 minutes; pour into ingots at 680°C.
[0061] S3. Heat treatment: keep at 420℃ for 24h.
[0062] S4. Extrusion: Use a horizontal extruder to extrude at a speed of 0.1 mm / s at 330°C with an extrusion ratio of 60; then cool naturally.
[0063] Example 2 : This embodiment provides a low-alloyed Mg-Zn-Ca magnesium alloy and a preparation method thereof.
[0064] A low-alloyed Mg-Zn-Ca magnesium alloy comprises the following element components in mass percentage: Zn 0.35%, Ca 0.26%, Fe<0.002%, Cu<0.0005%, Ni<0.0005%, Si<0.002%, and the balance is Mg.
[0065] The preparation method comprises the following steps:
[0066] S1. Ingredients: according to the proportion of magnesium alloy components, weigh high-purity Mg, high-purity Ca and high-purity Zn; the purity of metal Mg and Zn is greater than 99.98%, and the purity of metal Ca is greater than 99.9%.
[0067] S2. Melting and casting: melt the prepared magnesium alloy raw materials in sequence at 730°C under the protection of CO2+SF6 mixed gas (ratio 100:1) pure Mg, pure Ca and pure Zn, and keep warm for 50 minutes; refine and stir for 5 minutes, and keep warm and stand for 30 minutes; pour into ingots at 690°C.
[0068] S3. Heat treatment: keep at 420℃ for 16h.
[0069] S4. Extrusion: Use a horizontal extruder to extrude at a speed of 0.2 mm / s at 340°C with an extrusion ratio of 60; then cool naturally.
[0070] Example 3 : This embodiment provides a low-alloyed Mg-Zn-Ca magnesium alloy and a preparation method thereof.
[0071] A low-alloyed Mg-Zn-Ca magnesium alloy comprises the following element components in mass percentage: Zn 0.30%, Ca 0.22%, Fe<0.002%, Cu<0.0005%, Ni<0.0005%, Si<0.002%, and the balance is Mg.
[0072] The preparation method comprises the following steps:
[0073] S1. Ingredients: according to the proportion of magnesium alloy components, weigh high-purity Mg, high-purity Ca and high-purity Zn; the purity of metal Mg and Zn is greater than 99.98%, and the purity of metal Ca is greater than 99.9%.
[0074] S2. Melting and casting: melt the prepared magnesium alloy raw materials in the protection condition of CO2+SF6 mixed gas (ratio 100:1) at 720℃, melt pure Mg, pure Ca and pure Zn in turn, and keep warm for 40min; refine and stir for 5min, and keep warm and stand for 30min; pour into ingot at 400℃.
[0075] S3. Heat treatment: keep at 400℃ for 24h.
[0076] S4. Extrusion: Use a horizontal extruder to extrude at a speed of 0.3 mm / s at 320°C with an extrusion ratio of 40; then cool naturally.
[0077] Comparative Example 1 :
[0078] The difference from Example 1 is that the comparative example prepares an AZ31 magnesium alloy, which includes the following element components in mass percentage: Al 3.1%, Zn 1.0%, and the balance Mg.
[0079] The specific preparation process is the same as that in Example 1.
[0080] Comparative Example 2 :
[0081] The difference from Example 1 is that the Mg-Zn-Ca magnesium alloy prepared in this comparative example includes the following element components in mass percentage: Zn 0.57%, Ca 0.50%, Fe<0.02%, Cu<0.002%, Ni<0.002%, and the balance is Mg.
[0082] The specific preparation process is the same as that in Example 1.
[0083] Comparative Example 3 :
[0084] The difference from Example 1 is that the Mg-Zn-Ca magnesium alloy prepared in this comparative example includes the following element components in mass percentage: Zn 1.0%, Ca 0.50%, Fe<0.01%, Cu<0.002%, Ni<0.002%, and the balance is Mg.
[0085] The specific preparation process is the same as that in Example 1.
[0086] Comparative Example 4 :
[0087] The difference from Example 1 is that the Mg-Zn-Ca magnesium alloy prepared in this comparative example includes the following element components in mass percentage: Ca 1.0%, Zn 1.0%, Fe<0.01%, Cu<0.002%, Ni<0.002%, and the balance is Mg.
[0088] The specific preparation process is the same as that in Example 1.
[0089] Comparative Example 5 :
[0090] The difference from Example 1 is that in step S4, a horizontal extruder is used to extrude the product at a speed of 5 mm / s at 400° C., with an extrusion ratio of 60; and then the product is naturally cooled.
[0091] Comparative Example 6 :
[0092] The difference from Example 1 is that in step S4, a horizontal extruder is used, extrusion is performed at a speed of 2 mm / s at 150° C., and an extrusion ratio is 10; and then natural cooling is performed.
[0093] Comparative Example 7 :
[0094] The difference from Example 1 is that in step S4, a horizontal extruder is used, and the extrusion speed is 2 mm / s at 150° C., and the extrusion ratio is 60. The material has a large deformation resistance and cannot be extruded.
[0095] Test Example 1 :
[0096] This test example tests the mechanical properties and corrosion rates of the magnesium alloys in Examples 1 to 3 and Comparative Examples 1 to 6, and the specific values are shown in Table 1. The mechanical property test method is based on GB T 228.1-2021 and GB T 7314-2017 standards; the corrosion rate is the test result of the magnesium alloy sample being immersed in a 3.5% NaCl aqueous solution at room temperature for 48 hours, and after corrosion, chromic acid (200g / L CrO3+10g / L AgNO3) is used to clean the corrosion products on the surface of the sample, according to ASTM G1-90 standard.
[0097] Corrosion rate = (K×W) / (A×t×ρ)(1)
[0098] Where, K = 87600, W is the weight loss (g), A is the surface area of the sample (cm 2 ), t is the immersion time (h), ρ is the sample density (g / cm 3 ).
[0099] Table 1 Mechanical properties and corrosion rates of magnesium alloys
[0100]
[0101] It can be seen from Table 1 that the corrosion rate of the low alloyed Mg-Zn-Ca magnesium alloy (Examples 1 to 3) prepared by the present invention is less than 0.25 mm·y -1 , the corrosion resistance is better than that of high-purity magnesium; its tensile yield strength is ≥170MPa, tensile strength is ≥230MPa, and elongation is ≥36%. Figure 1 It can be seen that the magnesium alloy of Example 1 obtains a uniform and fine recrystallized structure (with an average grain size of about 6 μm) without an obvious second phase, and thus has good mechanical properties and corrosion resistance.
[0102] The magnesium alloys of Comparative Examples 1 to 4 have certain differences in composition relative to the present invention. Although the preparation methods are the same, their elongation and corrosion resistance are both deteriorated. Among them, the grains of the magnesium alloy of Comparative Example 2 are relatively coarse ( Figure 2 , the average grain size is about 8 μm). Example 1 and Comparative Example 2 use the same metallographic sample preparation process, but the surface corrosion of the sample in Comparative Example 2 is more serious and the overall performance is poor.
[0103] The alloy compositions of Comparative Examples 5 to 7 are the same as those of Example 1, but the forming processes of Comparative Examples 5 and 6 are different from those of the Example. The forming temperature of Comparative Example 5 is relatively high, and the grains are relatively coarse. Comparative Example 6 uses a small extrusion ratio and a forming temperature of 150°C, and the residual stress of the prepared material is relatively large, so the corrosion resistance of Comparative Examples 5 and 6 is relatively poor. Comparative Example 7 has a low forming temperature and a large deformation, and cannot be formed using conventional processes.
[0104] In summary, the low-alloyed Mg-Zn-Ca magnesium alloy provided by the present invention has good comprehensive mechanical properties, namely, high strength, excellent elongation and corrosion resistance, and can be used in the fields of magnesium alloy implantable medical devices, metal-air batteries, etc.
[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A low alloyed Mg-Zn-Ca magnesium alloy, characterized in that: The magnesium alloy is composed of the following elements in mass percentage: 0.2% to 0.5% Zn, 0.2% to 0.4% Ca, unavoidable impurity elements, and the balance is Mg.
2. The low alloyed Mg-Zn-Ca magnesium alloy according to claim 1, characterized in that: The atomic ratio of Ca to Zn is higher than 2:3; the total mass percentage of the inevitable impurity elements is not higher than 0.03%, among which: Fe<0.02%, Cu<0.002%, Ni<0.002%, Si<0.005%.
3. The low alloyed Mg-Zn-Ca magnesium alloy according to claim 1, characterized in that: The magnesium alloy is composed of the following elements in mass percentage: Zn 0.24-0.40%, Ca 0.22-0.28%, Fe<0.002%, Cu<0.0005%, Ni<0.0005%, Si<0.002%, and the balance is Mg.
4. The low alloyed Mg-Zn-Ca magnesium alloy according to claim 1, characterized in that: The magnesium alloy is composed of the following elements in mass percentage: Zn 0.32%, Ca 0.25%, Fe<0.002%, Cu<0.0005%, Ni<0.0005%, Si<0.002%, and the balance is Mg.
5. A method for preparing a low alloyed Mg-Zn-Ca magnesium alloy according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Mix various raw materials, and then melt and refine them in sequence under protective gas to obtain a melt; S2, casting the melt to obtain an ingot, and then performing heat treatment to obtain a billet; S3. The billet is extruded to obtain a formed part, and after cooling, a magnesium alloy is obtained.
6. The preparation method according to claim 5, characterized in that: In step S1, the raw materials are high-purity Mg, high-purity Ca and high-purity Zn; wherein the purity of metal Mg and Zn is greater than 99.98%, and the purity of metal Ca is greater than 99.9%.
7. The preparation method according to claim 5, characterized in that: In step S1, the protective gas is a mixture of CO2 and SF6, and the mixing ratio of CO2 and SF6 is 100-200:1; preferably, the mixing ratio of CO2 and SF6 in the protective gas is 100:1; Preferably, the smelting temperature is 720-760°C and the smelting time is 40-60 minutes; Preferably, the refining time is 5 to 20 minutes; after the refining, the mixture is kept warm and allowed to stand; further preferably, the standing time is 20 to 40 minutes; Preferably, during the refining process, the melt is stirred for 5 to 20 minutes.
8. The preparation method according to claim 5, characterized in that: In step S2, the casting temperature is 680-700°C; Preferably, the heat treatment temperature is 350-440° C., and the heat treatment time is 1-64 hours.
9. The preparation method according to claim 5, characterized in that: In step S3, the process of extruding the billet to obtain a formed part is specifically as follows: using a horizontal extruder, extruding at a speed of 0.05-0.5 mm / s; further preferably, the extrusion temperature is 250-350° C.; and the extrusion ratio is 10-80.
10. Use of the magnesium alloy according to any one of claims 1 to 4 in the fields of implantable medical devices and metal-air batteries.
